Copy Number Variation in Acetolactate Synthase Genes of Thifensulfuron-Methyl Resistant Alopecurus aequalis (Shortawn Foxtail) Accessions in Japan - Iwakami, Satoshi; Shimono, Yoshiko; Manabe, Yohei; Endo, Masaki; Shibaike, Hiroyuki; Uchino, Akira; Tominaga, Tohru (Frontiers in Plant Science, 2017)
Severe infestations of Alopecurus aequalis (shortawn foxtail), a noxious weed in wheat and barley cropping systems in Japan, can occur even after application of thifensulfuron-methyl, a sulfonylurea herbicide. In the present study, nine accessions of A. aequalis growing in a single wheat field were tested for sensitivity to thifensulfuron-methyl. Seven of the nine accessions survived application of standard field rates of thifensulfuron-methyl, indicating that severe infestations likely result from herbicide resistance. Acetolactate synthase (ALS) is the target enzyme of sulfonylurea herbicides. Full-length genes encoding ALS were therefore isolated to determine the mechanism of sulfonylurea resistance. As a result, differences in ALS gene copy numbers among accessions were revealed. Two copies, ALS1 and ALS2, were conserved in all accessions, while some carried two additional copies, ALS3 and ALS4. A single-base deletion in ALS3 and ALS4 further indicated that they represent pseudogenes. No differences in ploidy level were observed between accessions with two or four copies of the ALS gene, suggesting that copy number varies. Resistant plants were found to carry a mutation in either the ALS1 or ALS2 gene, with all mutations causing an amino acid substitution at the Pro197 residue, which is known to confer sulfonylurea resistance. Transcription of each ALS gene copy was confirmed by reverse transcription PCR, supporting involvement of these mutations in sulfonylurea resistance. The information on the copy number and full-length sequences of ALS genes in A. aequalis will aid future analysis of the mechanism of resistance.